“Students’ perceptions on learning vocabulary through total physical response (tpr) in efl classrooms” - Acurio Acurio, Alexandra Beatriz (2023)
When learning a language other than the mother tongue, it is essential to have a strong vocabulary since the more words learners know, the more they will be able to communicate assertively in both speaking and writing. However, many of them frequently struggle to quickly and easily internalize new vocabulary, especially when it is learned in an EFL setting. This situation prompts teachers to examine the existing teaching methods to select the most effective one to encourage the meaningful learning of vocabulary, which is the basis for second language proficiency. This study aims to identify the students' perceptions of learning vocabulary through Total Physical Response (TPR). The methodology applied was mixed; qualitative and quantitative. The participants were 35 elementary students in seventh grade from classes “A” and “B” at Mariano Negrete Catholic School in the academic period September 2022 - June 2023. The data collection instrument was a survey. The majority of students had favorable opinions of the Total Physical Response method for learning vocabulary, according to the data analysis. It was concluded that the use of movements, dynamics, and other activities of the TPR method significantly benefits vocabulary development in elementary school students since being in a stress-free environment makes them feel more relaxed and confident to practice the target language.